Linking E-cadherin mechanotransduction to cell metabolism through force mediated activation of AMPK - Bays, Jennifer L. (Nat Cell Biol, 2017)
The response of cells to mechanical force is a major determinant of cell behavior and is an energetically costly event. How cells derive energy to resist mechanical force is unknown. Here, we show that application of force to E-cadherin stimulates Liver Kinase B1 (LKB1) to activate AMP-activated protein kinase (AMPK), a master regulator of energy homeostasis. LKB1 recruits AMPK to the E-cadherin mechanotransduction complex, thereby stimulating actomyosin contractility, glucose uptake, and ATP production. The increase in ATP provides energy to reinforce the adhesion complex and actin cytoskeleton so the cell can resist physiological forces. Together, these findings reveal a paradigm for how mechanotransduction and metabolism are linked and provide a framework for understanding how diseases involving contractile and metabolic disturbances arise.